2016
DOI: 10.1111/jdv.13836
|View full text |Cite
|
Sign up to set email alerts
|

Neuropeptide Y expression in primary cutaneous melanoma

Abstract: High expression of NPY was associated with better prognostic histological parameters, low peritumoral mast cells density, presence of adhesion proteins and better outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…Nevertheless, in a study in which copy number variations of neuropeptide and receptor genes were investigated for multiple cancers, the expression of NPY and its receptors, Y1R , Y2R , and Y5R , were given negative prognostic Z-scores in cutaneous melanoma ( 110 ). Having negative prognostic scores in this study indicates that the expression of NPY and its receptors in cutaneous melanoma is associated with favorable survival outcomes for patients, which is in agreement with the findings from Pérez Tato and colleagues’ clinical study of NPY expression in primary cutaneous melanomas ( 86 ).…”
Section: Genetic Associations Of Npy With Skin Pathologysupporting
confidence: 91%
See 1 more Smart Citation
“…Nevertheless, in a study in which copy number variations of neuropeptide and receptor genes were investigated for multiple cancers, the expression of NPY and its receptors, Y1R , Y2R , and Y5R , were given negative prognostic Z-scores in cutaneous melanoma ( 110 ). Having negative prognostic scores in this study indicates that the expression of NPY and its receptors in cutaneous melanoma is associated with favorable survival outcomes for patients, which is in agreement with the findings from Pérez Tato and colleagues’ clinical study of NPY expression in primary cutaneous melanomas ( 86 ).…”
Section: Genetic Associations Of Npy With Skin Pathologysupporting
confidence: 91%
“…There was also a slight positive correlation between NPY expression and tumor cell proliferation. In a follow-up study, Perez Tato and colleagues evaluated 79 primary tumors and found that superficial spreading melanoma and lentigo maligna exhibit significantly higher levels of NPY expression in comparison to nodular melanoma ( 86 ). However, in contrast to Gilaberte et al these authors report low NPY expression associated with high proliferation, increased metastasis, high peritumoral mast cell density, and reduced patient survival, but no relationship between NPY expression and intratumoral lymphocyte infiltration.…”
Section: Expression Of Npy Protein In Skin Pathologymentioning
confidence: 99%
“…The multifaceted role of the NPY system in tumours and its differential function are driven by the variability in the receptor signalling pathways and peptide expression (Tilan and Kitlinska 2016 ). The presence of NPY and its receptors was described in several neoplasms, such as PCa, breast cancer, melanoma, hepatocellular carcinoma (HCC), cholangiocarcinoma, neuroblastoma, Ewing sarcoma and pituitary adenoma (Reubi et al 2001 ; Kitlinska et al 2005 ; Levy et al 2006 ; DeMorrow et al 2011 ; Hong et al 2015 ; Lv et al 2016 ; Pérez Tato et al 2017 ). However, tissue expression of NPY receptor network has not been investigated in detail.…”
Section: Discussionmentioning
confidence: 99%
“…3d ) and expression of NPY in melanoma has been associated with nodular melanomas with vertical growth, metastasis and decreased lymphocyte infiltration ( Gilaberte et al , 2012 ). Note however, that the same group later linked NPY expression to good prognosis outcome ( Pérez Tato et al , 2017 ), indicating a complex role of NPY in melanoma. AXL was also found to make interactions using the molecular ligand adrenaline to β2 and α1A adrenoreceptors ( Fig.…”
Section: Resultsmentioning
confidence: 99%